The success factors for Government Information Sharing (GIS) in natural disaster management and risk reduction - Ahmad Dahlan, Abdul Rahman; Mohd Dahan, Hayati; Mohd Saman, Md Yazid (2013)
The frequency of natural disasters has been increasing for the last 30 years in the world, having caused great damages/losses. Among those damages/losses, about 90 % are concentrated in the Asian region where natural disasters are one of the serious issues not only for humanitarian but also for economic and industrial point of view. These bring about the loss of lives, property, employment and damage to the physical infrastructure and the environment. Disaster management (DM) including risk reduction efforts aim to minimize or avoid the potential losses from hazards, assure prompt and appropriate assistance to victims of disaster, and achieve rapid and effective recovery. While information, knowledge and resources sharing can enhance the process of DM, there is a perceived gap in government collaboration and coordination within the context of natural DM. Identifying potential success factors will be an enabler in managing disasters. The objective of this paper is to present the literature findings on success factors that ensure government information sharing quality in supporting effectively DM. Accordingly the identified factors were classified into major categories, namely political leadership support, inter-agency collaboration, individual agency capacity including ICT, and agency benefits.